A novel and efficient method for punicic acid-enriched diacylglycerol preparation: Enzymatic ethanolysis of pomegranate seed oil catalyzed by Lipozyme 435. (1st April 2022) - Zhou, Duan; Zhao, Mouming; Wang, Jiankang; Faiza, Muniba; Chen, Xuefeng; Cui, Junjie; Liu, Ning; Li, Daoming
Abstract: Punicic acid (PA)-enriched diacylglycerol (DAG) possesses both the beneficial effects of PA and DAG. However, few studies have focused on the preparation of PA-enriched DAG. Here, we report a novel and highly efficient method for the preparation of PA-enriched DAG through Lipozyme 435-catalyzed ethanolysis of pomegranate seed oil (PSO). Firstly, PSO was obtained through microwave-assisted extraction. Subsequently, four lipases were screened for their capability in the preparation of PA-enriched DAG through ethanolysis of PSO (containing 82.98% PA), and Lipozyme 435 was selected. Under the optimal conditions, the resultant mixture containing 32.86% DAG was obtained. Interestingly, Lipozyme 435 maintained superior operational stability after ten successive cycles. A scale-up reaction was then conducted under the optimized conditions and the purified product containing 51.83% DAG (containing 81.95% PA) was obtained. The final product with a low peroxide value (1.45 mmol/kg) and undetectable acid value reached edible quality. This is the first study for the preparation of PA-enriched DAG through ethanolysis and Lipozyme 435 exhibited superior capability and recyclability. Compared with other approaches for DAG preparation, this approach favored shorter reaction time and better quality of the product. This study provides useful information for further studies involving DAG preparation and modification of PSO. Highlights: PA-enriched DAG was prepared through modification of pomegranate seed oil for the first time. Enzymatic ethanolysis is a novel and potent approach for PA-enriched DAG preparation. Lipozyme 435 exhibited superior capability and recyclability during ethanolysis. The proposed novel approach favored shorter reaction time and better quality of the final product.